Plantar Angioleiomyoma Masquerading as a Hyperkeratotic Lesion: A Case Report - Jiandi Wang; Tingting Zhao; Qu Liu; Jun Song (Clinical Case Reports, 2026)
ABSTRACT Plantar angioleiomyoma may mimic a refractory hyperkeratotic lesion such as a corn. Progressive enlargement, persistent weight‐bearing pain, and failure of keratolytic therapy should prompt further evaluation. Doppler ultrasonography can help identify a deep vascular tumor and guide definitive excision, and histopathological examination remains essential for definitive diagnosis.